KETEPATAN MODEL FINANCIAL DISTRESS DALAM BISNIS JASA KEUANGAN - Edi Edi; Natalis Christian; Aviany Santi (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The research was formulated to identify and assess models capable of measuring financial distress in the financial sector during the Covid-19 pandemic, considering the potential rise in financial challenges encountered this sector at the pandemic's onset and throughout its duration. Models such as Altman, Springate, Zmijewski, Grover, Fulmer, Ohlson, and CA Score served as instrumental tools in the study. The survey employed quantitative approach targeting population of 79 financial sector companies listed on Indonesian Stock Exchange from 2019 to 2021, with sample of 64 firms selected through purposive sampling method. Data analysis involved panel regression utilizing Eviews continued with SPSS software due to significant data deviations. Conducted comprehensive suite of statistical tests including descriptive statistics, outlier tests, chow tests, hausman tests, F tests, adjusted R tests, and t tests. Findings indicated the efficacy of Altman, Springate, Zmijewski, and Fulmer models identifying challenging financial conditions within financial sector companies. Conversely, the Grover, Ohlson, and CA Score models did not yield significant findings in measuring financial challenges within the sector. T-statistics underscored that the Springate model emerged as the most effective, achieving the highest score among all models at 2.769227, followed by the Zmijewski, Altman, Fulmer, Grover, CA Score, and Ohlson models. Keywords: Financial Distress, Altman, Springate, Zmijewski, Grover